The Inner and Outer Qualities of Extracellular Vesicles for Translational Purposes in Breast Cancer - Schwich, Esther; Rebmann, Vera (Frontiers in Immunology, 2018)
Breast cancer (BC) is the second most common cause of cancer mortality of women worldwide. BC is a systemic disease with a highly heterogeneous course of disease. Therefore, prognostic and diagnostic biomarkers are required to improve the clinical risk management. Cancer-derived or cancer-associated extracellular vesicles (EVs) procured from the bloodstream of BC patients offer a novel platform for the qualitative and quantitative screening and establishment of biomarkers. Here, we focus on common aspects of EVs, on the function of BC-derived EVs and their translational potential considering the EV abundancy, intravesicular as well as outer membrane-anchored composition and current challenges of implementation in clinical practice.